Becoming Indivisible in the Age of Cloning: Resistance, Individuality, and Photography in Notre vie dans les forêts - Stojanovic, Sonja (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2020)
After broaching the topic in two short stories included in the collection Zoo (2006) – “Quand je me sens très fatiguée le soir” and “Mon mari le clone” – Marie Darrieussecq, in her most recent novel Notre vie dans les forêts (2017), returns to the question of clones. In an age when high-tech surveillance and meticulous tracking mechanisms have become the norm, in a world where clones are used as spare parts to prolong one’s life, a group of rebels decides to resist and liberate their cloned halves, only to find out that they are also clones themselves; from their hiding place in a forest, the dying female narrator writes her story in a notebook hoping she will be remembered. This article considers how clones can be said to have a distinct and unique identity by tracing the evolution of the female narrator  from clone to individual. It also proposes to read the novel as a powerful series of snapshots that allow the narrator, through her photographic writing, to become her own ghost, as opposed to someone else’s clone.